Processo eletrônico frente aos princípios da celeridade processual e do princípio do acesso à justiça - Silva, José Maria Cavalcante da (2015)
This study is literature and deals with Electronic Process Faced with the principles of Celerity Procedure and. Access to Justice in order to expedite the judicial process, the use of electronic media, without, at the expense of the general access to justice in a confrontation between the cited principles Access to justice must be broad citizens. Constitutional Amendment No. 45, added device in the Constitution, ensuring all the reasonable duration of the process, but also means that guarantee speed in the procedure. The 1988 Constitution increased the amount of individual fundamental rights. To that end, we analyze the possibilities of access to justice and speedy trial and development challenges of the new method, which replaced the case of paper, for totally electronic records, pursuant to Law 11,419 / 2006 Electronic Process Law. And judicial reform a way to improve speed and access to justice claimed by all of society.